Thematic Learning in Kindergarten Based on Al-Islam Kemuhamadiyahan and Local Wisdom - Duriani Duriani; Bahaking Rama; Hadi Pajarianto; Puspa Sari (LPPM Universitas Pahlawan Tuanku Tambusai, 2021)
This research is motivated by the preservation and implementation of religious values and local wisdom, it is a case study with a qualitative approach, where the data collected from observation and interviews. The results showed that the Al-Islam kemuhammadiyahan and local wisdom value had been described in the lesson plan and the learning implementation. The value of the Dewata Seuwae is a form of instilling faith in children by introducing Allah creation, the holy book, and the Prophet. The values of alempureng and amaccangang are instilled so that they are always honest. Agettengeng means adherence to principles and responsibility to the ummah, nation, and state. The value of aperrukeng is a child's primary asset for cooperation and a sense of caring for the people around them. This research proves that religion and culture can coexist harmoniously, and their values can be used in thematic Learning in early childhood